Tradisi Perkawinan Adat Suku Sahu Dalam Perspektif Teologi Kristen di Jemaat GKPMI, Halmahera Barat - Ngamon, Daud A; Nendissa, Julio Eleazer; Rares, Freby M. (Litbang STFT Widya Sasana Malang, 2024)
The interaction of Christianity along with the traditions that have developed since the arrival of Christianity in North Maluku, so that the harmonization of Christian teachings and the traditions of the Sahu tribe's traditional marriage in life practices is still reflected in daily activities. The author uses qualitative descriptive analysis with theological, historical, sociological, and anthropological approaches. The research findings indicate that the stages and processes of the Sahu tribe's traditional marriage are moloara siri or osam golo'o, which consist of several phases, namely: di'dingoto (delivery), haka waro (finding out), golo'o masomoar (entering and asking for the usual), silolara, (leveling), oro namo ma ngina (taking the bride and traditional party). Then moloara masibidi (elopement), moloaramasingata'a or osam ino (marriage by delivering oneself), moloara ngali ngasu'u (marriage by changing poles), moloara tatanu (marriage by enslaving oneself in the mother-in-law's house), moloar si cako'o (elopement/raided), moloara rabasa ngowa'a manga were'a (marriage by stealing someone else's wife/husband). The acculturation of the Sahu tribe's customary marriage to Christian marriage has become one result, the essence of the Sahu tribe's customary marriage tradition blends with the Christian marriage system, and the Christian marriage system is harmonized with the Sahu tribe's customary marriage tradition, and the customary marriage system, church marriage, and government complement each other and become inseparable from these stages